Impact of gossypin on gene expression of HSP60 and HSP70 in different cancer cell lines - DİRİCAN, Ebubekir; ÇINAR, İrfan (Cukurova Medical Journal, 2022)
Purpose: The aim of this study is to evaluate the impact of gossypin on the expression level of heat shock proteins (HSPs) genes in different cancer cells. Materials and Methods: Cells were grown under standard culture conditions. Cancer cells were treated with different concentrations (5-100 µg/ml) of gossypin and cisplatin (50 µM) as positive control. Cell viability and effective dose range (5-100 µg/ml) of gossypin were determined by MTT at 24, 48 and 72 hours. After RNA isolation and cDNA synthesis, HSP60 and HSP70 gene expression levels were analyzed using RT-PCR. For gene expression analysis, the 2-∆∆ct method was used. Results: According to the MTT results, 25-50-100 µg/ml of gossypin doses were found effective on HSP60 and HSP70 gene expression levels in the cancer cell lines. Gossypin affected with dose-dependently the expression of HSP60 and HSP70 in the three cell lines. In the three cell lines, 50 µg/ml and 100 µg/ml of gossypin doses significantly reduced the expression of HSP60 and HSP70 compared to control group. Conclusion: Our results strongly supported the anticarcinogenic effect of gossypin at various doses in different cell lines. However, we believe that further in vivo research and human studies are needed. Our findings suggest that gossypin could be suitable candidate agent for further investigation to develop new strategies for the prevention and/or treatment of different cancer types.
Keywords: Klinik Tıp Bilimleri; Gossypin; HSP60; HSP70; MCF7; PC3; Hep3b; Clinical Sciences; MCF7; Hep3b; Gossypin; PC3; HSP60; HSP70; 3. Good health